Perancangan dan Pengembangan Vıdeo Katalog Produk Pada Toko Byzen - Mangapul Siahaan; Oktavina Oktavina (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
Byzen Store is a business that is engaged in selling kitchen items such as drinking bottles, food containers, jars, and other items with the majority of goods from the Tupperware brand which has been running for 10 years. The obstacle faced by Byzen Stores is the lack of creativity in doing promotions. Applied research methodology is the method used in this research with the aim of finding solutions to problems faced by society, or industrial and business organizations. The method used in designing this promotional is Media Production Concept (KPM) method which has 3 stages, namely Pre-Production, Production, and Post-Production. The tools are Adobe Photoshop CS6, Adobe Premiere Pro 2020, and Canva Pro. The results of this research are in the form of a promotional video containing photos of product from the Byzen Store. The implementation of the research resulted in many positive impacts where the owner of the Byzen Store felt an increase in sales and the Store became more known to the wider community.